Does the use of black ink still comprise the “darkest” issue of CMYK printing? - Kuznetsov, Yuri; Ermoshina, Maria (Journal of Print and Media Technology Research, 2023)
Black ink can be used for multicolor printing to different extent within each of such multiple purposes, as: replacement of the achromatic component of three chromatic inks combination; reproduction of the image achromatic colors; expanding the color gamut; providing print security features … The relationships and effects within these functions are discussed in the paper on the background of prepress facilities evolution starting from the times of photoengraving and analogue scanners of 60’s up to the precise digital color control of today. The results of comparative colorimetric analysis of the sets comprising cyan, magenta and yellow (CMY), and cyan, magenta, yellow and black (CMYK) revealing the black in particular effect of expanding the print gamut by providing the darker chromatic colors which aren’t available for any combination of the other three process ones are also presented.